THE RELATIONSHIP BETWEEN CONSUMER INVOLVEMENT WITH BRAND AWARENESS IN THE PROCUREMENT OF SAMSUNG SMARTPHONE - Rahmi, Fitria; Sarry, Septi Mayang; Boer, Novrizal Riady (Universitas Islam Negeri Imam Bonjol Padang, 2016)
A brand must be remembered by consumers for helping them when deciding to buy a product. This is related to brand awarenness which is owned by the consumer. Brand awareness is the ability for consumers to recognize and remember enough details of a brand in a given category to make it easier to buy. In this case the role of the process of storing information into the memory becomes important and one of the aspects associated with information processing is consumer involvement.This study describe the relationship between consumer involvement with the brand awareness in the purchase of Samsung Smartphone among teenagers in Padang City. The subject of this research were 150 teenagers in Padang City, the data obtained by using non-probability sampling with accidental sampling technique. Data was obtained using brand awareness scale with reliability coefficient on 0,904 and consumer involvement scale with reliability coefficient on 0,901. The data analyzed using correlationproduct moment pearson test.Data obtained by correlation analysis the result of this research showed the correlation coefficient (r) of 0.609 and a significant number which was 0.000 (p <0.05). The results of this analysis indicated that thereis a positive relationship between consumer involvement with the brand awareness in the purchase of Samsung Smartphone among teenagers in Padang City, it is means higher consumer involvement of a person, the higher brand awareness that one has,and when consumer involvement of a person is low, then the brand awareness of a person will be low.A brand must be remembered by consumers for helping them when deciding to buy a product. This is related to brand awarenness which is owned by the consumer. Brand awareness is the ability for consumers to recognize and remember enough details of a brand in a given category to make it easier to buy. In this case the role of the process of storing information into the memory becomes important and one of the aspects associated with information processing is consumer involvement.This study describe the relationship between consumer involvement with the brand awareness in the purchase of Samsung Smartphone among teenagers in Padang City. The subject of this research were 150 teenagers in Padang City, the data obtained by using non-probability sampling with accidental sampling technique. Data was obtained using brand awareness scale with reliability coefficient on 0,904 and consumer involvement scale with reliability coefficient on 0,901. The data analyzed using correlationproduct moment pearson test.Data obtained by correlation analysis the result of this research showed the correlation coefficient (r) of 0.609 and a significant number which was 0.000 (p <0.05). The results of this analysis indicated that thereis a positive relationship between consumer involvement with the brand awareness in the purchase of Samsung Smartphone among teenagers in Padang City, it is means higher consumer involvement of a person, the higher brand awareness that one has,and when consumer involvement of a person is low, then the brand awareness of a person will be low.